Noites pioneiras do ensino superior noturno em Sergipe : memórias da fundação do curso de pedagogia na Faculdade Pio Décimo (1976-1980) - Viana, Sônia Maria de Azevedo (2020)
This thesis entitled “Pioneer Nights of Higher Education in Sergipe: memories of the founders of the pedagogy course at Faculdade Pio Décimo (1976-1980)”, is linked to the line of research - History, Society and Educational Thinking, which is part of the Education Program PostGraduation in Education at the Federal University of Sergipe. It aimed to understand the history of the foundation of Faculdade Pio Décimo, as a pioneer institution in offering the first night course of pedagogy in Sergipe. Using the methodology of oral history and studies that correlate and differentiate history and memory, the work was developed from the narratives of the director memories, five professors and two founding employees, highlighting the way of organization, conditions and challenges posed for the functioning of this first class of pedagogues, from 1976 to 1980, determined within the limits of the beginning and conclusion of the first class of the course in question. The central problem was thus outlined: With the foundation of the FPD, the implementation of the Pedagogy course, recognizing, from the narratives of its founders, the way of organization and functioning of the first class; the definition of the curriculum proposal; the accomplishment of pedagogical practices and the general conditions and challenges for the creation of the institution and the opening of the pedagogue's training course? In the same vein: How were they selected and how was the life, training and performance trajectories of the founders of the FPD pedagogy course? What historical marks were left in their memories about the pedagogical organization, educational practices, relationships and actions developed during the first years of working in the night course? What could be reconstructed from the emergence of the higher education course in Pedagogy based on the narratives of the teachers, director and founding employees? Thus, we defend the thesis that the history of institutional life is collective, and it is not built just as an organized set of academic knowledge and bureaucratic procedures, – moreover – it is established in the intertwining of life stories, and in individual memories, which keep and update the meaning of training experiences, always open to new interpretations and production of meanings, because they are not limited to the temporality of what has been lived as the past, but involves the dynamic relationship past / present / future, such as movement and recreation in the elapse of historical time. The results obtained revealed the importance of this process of reminiscing about the past, and provided an opportunity for a re-reading of the institution, giving new meanings to the knowledge, procedures and practices learned in the context of the experiences shared within the scope of the pedagogy course, as a common place of action for those involved in research, instigating new searches and promoting greater understanding of the training processes that took place in the context of night higher education in Sergipe, particularly in a private institution, therefore constituting an institutional memory.